Fast report: surface deformation associated with the 2025 Dapu earthquake - Zixin Lee; Ray Y. Chuang; I-Ting Wang; Lishiue Chen; Wu-Lung Chang; Chi-Yu Chiu; Kuo-En Ching; Sheng-Wei Guo; Chien-Liang Chen (Terrestrial, Atmospheric and Oceanic Sciences)
Abstract On January 20th of 2025, a M6.4 earthquake struck the Dapu area in southwestern Taiwan. The event caused damage in Chiayi County and Tainan City, particularly in Nanxi District, where surface deformation was anticipated. In response, we conducted a rapid geodetic survey to investigate coseismic displacement fields from GNSS and InSAR observations. The result indicates surface displacements of up to several centimeters without visible interferogram discontinuity. To assess the fault slip, we applied a half-space dislocation model to evaluate two possible fault planes: a west-dipping and an east-dipping fault, both derived from the AutoBATS focal mechanism. Additionally, we analyzed pre-seismic surface deformation by using GNSS and InSAR time series data. Our findings reveal a high shortening rate (> 35 mm/yr) across the western foothills at this latitude without an obvious velocity gradient around the epicenter. These results enhance our understanding of the fault dynamics in southwestern Taiwan and highlight the critical role of geodetic data in seismic hazard assessments.